2006
DOI: 10.1016/j.stam.2006.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of hard spheres under gravity by Monte Carlo simulation

Abstract: Monte Carlo simulations were performed for hard spheres (HSs) under gravity. The gravity was increased stepwise. HSs were placed between the bottom and the top hard walls. For g*R0.9, we observed that a 'sediment' was comprised of two crystalline and one fluid regions. Here, g* is defined by g*Zmgs/k B T with m being the mass of a particle, s the HS diameter, g the acceleration due to gravity, and k B T the temperature multiplied by Boltzmann's constant. The bottom crystal was less defective or well-ordered an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Moreover, we have already found a configuration which was succeeded in newly grown crystal in the fluid phase in simulations of the same condition [17]. In addition, we confirmed that a coherent growth occurred in the simulations [18]. Complementarily to the simulations, we have given elastic energy calculations to understand the driving force of upward move of the Shockley partial dislocation [19,20].…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Moreover, we have already found a configuration which was succeeded in newly grown crystal in the fluid phase in simulations of the same condition [17]. In addition, we confirmed that a coherent growth occurred in the simulations [18]. Complementarily to the simulations, we have given elastic energy calculations to understand the driving force of upward move of the Shockley partial dislocation [19,20].…”
Section: Introductionsupporting
confidence: 73%
“…The separation between neighboring groove edges was 0:338s. Accordingly, the periodicity of the lattice was 1:045s and the diagonal distance 1:478s; i.e., we set the bottom lattice so as to coincide with the bottom (0 0 1) layer of the fcc crystal of the previous flat wall simulation [18].…”
Section: Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other point characteristic of these simulations is that the coherent growth [12] occurred as already mentioned. We find that the lattice constant c increases linearly with the altitude z whereas the lattice constants a ¼ b are constant.…”
mentioning
confidence: 64%
“…Although numerical estimation has been carried out using an elastic constant for the HS crystal, this effect is not limited to colloidal crystals. However, the condition of coherent growth (which was reported in Reference [77]) was used. The glide mechanism of a partial dislocation for the reduction of stacking disorder was revealed in Reference [74].…”
Section: Sedimentationmentioning
confidence: 99%